The influence of entrepreneurship courses on entrepreneurial interest in PGSD students in the globalization era - Andini, Tri Ayu; Zamhari, Ahmad; Rahmawati, Rahmawati; Maulidina, Luthfiyah; Tasia, Tasia (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2023)
The problem of unemployment is one of the critical problems in Indonesia that is still difficult to overcome, because of the continuous increase in population, not balanced with the increase in employment. Companies are increasingly selective in accepting new employees, but the interest of Indonesia's young generation in entrepreneurship is currently relatively low. In this condition, the world of education has the responsibility to increase the interest in entrepreneurship of the younger generation. This study aims to determine the influence of entrepreneurship courses on the entrepreneurial interest of PGSD students. The research method used is qualitative descriptive. With data collection techniques using questionnaires and interviews on subjects, namely PGSD students of PGRI Palembang University semester 4 as many as 10 people were taken randomly. The results of this study show that there is an influence of entrepreneurship on the entrepreneurial interest of PGSD students in this era of globalization. So, it can be concluded that entrepreneurship courses can increase entrepreneurial interest among PGSD students of PGRI University.